ON THE EFFECT OF WATER FLOW SPEED TO HYDRODYNAMIC RESISTANCE FORCE OF GILLNET; MODEL NET EXPERIMENTS IN THE FLUME TANK - Bambang Murdiyanto; Desty Maryam; Hasan Basri (Research Center for Fisheries, 2010)
When gillnet is operated in the sea its will encounter the effects of seawater current and tidal movements. The shape and construction of the gillnet will be effected by the direction and flow speed of the seawater current. When the current is strong enough the gillnet shape could be changing, falling down or even roll up.